Antitumor efficacy of 5-aminolevulinic acid (5-ALA)-based radiodynamic therapy under single-dose X-ray irradiation in colon cancer - Takahashi, Junko; Nagasawa, Shinsuke; Wang, Xiupeng (Frontiers in Oncology, 2025)
Introduction5-Aminolevulinic acid (5-ALA)-based radiodynamic therapy (RDT), an experimental approach that combines systemic administration of 5-ALA with ionizing radiation, has demonstrated antitumor efficacy primarily in preclinical studies using fractionated irradiation protocols. In recent years, single-dose and hypofractionated irradiation regimens have been increasingly adopted in clinical radiotherapy; however, the therapeutic potential of 5-ALA-based RDT under single-dose irradiation conditions remains to be elucidated.MethodsWe evaluated the accumulation of protoporphyrin IX (PpIX) in human colon cancer HT-29 cells compared with previously studied cell lines, mouse melanoma B16/BL6 and human glioblastoma U-251 MG, U-87 MG in vitro. Using a HT-29 xenograft mouse model, we investigated the antitumor efficacy of a single 12 Gy X-ray dose combined with 5-ALA at doses of 100 or 200 mg/kg. Tumor growth, histopathological alterations, and immune cell infiltration were analyzed. Gene expression profiles of tumor tissues were examined by microarray analysis at day 29 post-irradiation.ResultsHT-29 cells exhibited equal or greater PpIX accumulation compared with other tumor cell lines. In vivo, single-dose X-ray irradiation (12 Gy) combined with various doses of 5-ALA resulted in 5-ALA dose-dependent suppression of tumor growth. Notably, administration of 200 mg/kg 5-ALA plus 12 Gy X-ray induced marked tumor regression in all animals without statistically significant weight loss. Histopathological analysis demonstrated disruption of tumor cell islands and increased infiltration and proximity of Iba1-positive immune cells to tumor cells. Microarray analysis identified 75 differentially expressed genes between untreated and 200 mg/kg 5-ALA plus X-ray groups, including downregulation of genes involved in DNA repair, tumor suppression, autophagy, cell cycle regulation, metabolism, and immune evasion.ConclusionThis study demonstrates for the first time that 5-ALA combined with single-dose X-ray irradiation exerts a strong antitumor effect on HT-29 xenografts. The observed effects may be mediated by induction of immunogenic cell death, modulation of the tumor microenvironment, and suppression of tumor cell survival pathways. These findings highlight single-dose 5-ALA-based RDT as a potential novel therapeutic strategy.